Comparative study on the physico-chemical status among intact, disturbed and die-off mangrove areas of Bongsanglay Mangrove Natural Park - DE LOS REYES, CRISTINA MARIE (Archīum Ateneo, 2017)
This study surveyed the vegetation of three mangrove sites namely intact, disturbed and die-off mangrove areas and compared their physico chemical conditions of soil and water to determine if any of these parameters could be used as screening tool to indicate mangrove mortality.Disturbed (MDIS) area showed significant difference among mangrove areas with the highest temperature 31.33 oC 2.08 (P<0.05) and salinity 41.00 1.73 (P<0.05) during dry season. Die-off (MDO) area showed significantly lower pH as compared to other mangrove area. This area is greatly dominated with Rhizophora spp. which is more acid-tolerant and can be found in lower pH, which indicates that dying off of mangrove species cannot be attributed to the water pH. Organic matter and organic carbon content of the soil was significantly higher in MDO than the other areas. Results also showed that lowest values of total nitrogen 0.17%, which is necessary in the growth of mangroves and available phosphorus of 8.12%, which is important in the development of leaf and stem were measured in intact area, the area that showed most diverse and at best vegetation state. The study concluded that there is likely to be no single measure that could determine the difference in the health status of mangrove stands and adequately explain the cause of the die-off of the mangroves.